2020
DOI: 10.1186/s12894-020-00654-x
|View full text |Cite
|
Sign up to set email alerts
|

The Pros and cons of balloon dilation in totally ultrasound-guided percutaneous Nephrolithotomy

Abstract: Background: To evaluate the feasibility and safety of balloon dilation (BD) in totally ultrasound-guided percutaneous nephrolithotomy (PCNL). Methods: The data of 95 patients underwent BD were collected in this retrospective study between August 2016 and December 2018. During the same period, telescopic metal dilation was used in 1161 patients. Ninety five patients were selected as the control group and matched at a 1:1 ratio to index balloon dilation (BD) cases in regards to Guy's stone score, age, sex, BMI, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…This was supported by those studies of mini-PCNL (13,14), in which the failure rate of serial dilation up to 18 Fr was generally less than 5%. On the contrary, the tips of large-sized Amplatz dilators are relatively blunt and tend to push the kidney away before they enter the collecting system, which causes a status of short dilation (15,16). Second, all the small-sized (8-Fr to 16-Fr) Amplatz dilators were advanced at a fixed depth as measured earlier.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This was supported by those studies of mini-PCNL (13,14), in which the failure rate of serial dilation up to 18 Fr was generally less than 5%. On the contrary, the tips of large-sized Amplatz dilators are relatively blunt and tend to push the kidney away before they enter the collecting system, which causes a status of short dilation (15,16). Second, all the small-sized (8-Fr to 16-Fr) Amplatz dilators were advanced at a fixed depth as measured earlier.…”
Section: Discussionmentioning
confidence: 99%
“…In another study with 207 cases undergoing ultrasoundguided balloon dilation, the success rate of tract dilation on the first attempt was 88.4% (11). Short dilation was considered to be the main cause of failure with balloon dilation (15,16). Obesity was reported to predict failure of ultrasound-guided balloon dilation, as it was reported that the success rate was 76.9% in normal weight and 79.0% in overweight, but it was only 45.7% in obese subjects (6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The continuous compression of injured vessels in the tract during balloon dilatation resulted in less blood loss [9]. Although balloon dilatation has many advantages in establishing tract, there are still some problems such as too shallow dilation (short dilation), too deep dilation and tract displacement in the process of dilatation, resulting in serious complications such as tract establishment failure, bleeding and renal parenchyma injury, especially in the patients without hydronephrosis [10,11] and obesity [12]. The correct puncture path and reasonable expansion method are effective methods to reduce the amount of blood loss [13].…”
Section: Discussionmentioning
confidence: 99%